Takopi's original sin - Taizan5; Roman, Annette (VIZ Media, 2021)
Takopi travels from his home of Happy Planet to spread happiness across Earth, but meets the unsmiling Shizuka upon landing. Her friends at school and home life seem to be the source of her somber expression and the pure-hearted Takopi is determined to change things for the better! But what truths await him when the curtains rise in this shocking drama?! --